The Effect of Digital Literacy and Self-Regulated Learning on Students’ Academic Achievement at Saiburi ChaengPrachakarn School, Pattani, Southern Thailand - Erdiansyah; Ainun Mardiyah Lubis; Syahruddin Aritonang; Mayeeta Hawae; Aslamiyah Rambe (Jurnal Penelitian Pendidikan IPA, 2026)
This study examined the effects of digital literacy and self-regulated learning on students’ academic achievement at Saiburi ChaengPrachakarn School, Pattani, Southern Thailand. A quantitative explanatory correlational design was employed with 30 secondary school students selected through proportional random sampling. Data were collected using validated questionnaires on digital literacy and self-regulated learning, while academic achievement was measured using students’ semester examination scores. Descriptive statistics and multiple linear regression were used for data analysis. The findings revealed that digital literacy positively and significantly influenced academic achievement (β = 0.491, p < 0.05). Self-regulated learning also had a positive and significant effect (β = 0.503, p < 0.05). Simultaneously, both variables significantly predicted academic achievement (F = 304.077, p < 0.001), explaining 95.7% of the variance (R² = 0.957). These results indicate that students with stronger digital competence and self-regulated learning skills achieve better academic outcomes. Strengthening both competencies is therefore essential for improving academic performance in technology-integrated secondary education.